The Merchant of Venice: An Allegorical Equation of Art and Commodity - Pakdamanshahri, Fatemeh (Sara) (Advances in Social Sciences Research Journal, 2020)
John Cage narrates: “...Somebody said that Brecht wanted everybody to think alike. I want everybody to think alike... Everybody looks alike and acts alike, and we’re getting more and more that way. I think everybody should be a machine. I think everybody should be alike.” The interviewer asks Cage: “Isn’t that like pop art?” And consequently, Cage responds: “Yes, that’s what pop art is, liking things.”1 Shakespeare’s plays have long been put under scrutiny, praised, and devalued through various theoretical lenses. Regardless of the innumerable doctrines against which his tragedies and comedies have been over-analyzed, tending to his art in terms of the essence of his works, the artistry of them seems more than crucial. Morality, ethics and individual and collective philosophical readings of Shakespearean plays have coexisted with and mirrored in words, hence literature. There seems to be no way out but to weigh Shakespearean plays against these impossibly heavy concepts. This paper intends to undergo an ethical reading of The Merchant of Venice, through the ideas of Emmanuel Kant and Jeremy Bentham. Consequent to the ethical reading of The Merchant of Venice, the artistic value(s) of it will be discussed; whether one is blessed with an artistic sense or otherwise is a question to be tended to.